The Value of P‐Wave Parameters Changes in Predicting Catheter Ablation Outcomes for Paroxysmal Atrial Fibrillation - Ibrahim Antoun; Xin Li; Zakariyya Vali; Ahmed Kotb; Ahmed Abdelrazik; Ivelin Koev; Riyaz Somani; G. André Ng (Annals of Noninvasive Electrocardiology)
ABSTRACT Background Pulmonary vein isolation (PVI) is the most promising management method for paroxysmal atrial fibrillation (PAF). The P wave in the electrocardiogram (ECG) represents atrial depolarization. This study aims to correlate P‐wave parameters after PVI with outcomes. Methods This single‐center retrospective study included consecutive patients with first‐time PVI for PAF between 2018 and 2019 and targeted pulmonary veins (PVs). Procedure success was defined by freedom of ECG‐documented AF at 12 months. Digital 12 leads ECGs with 1–50 hertz bandpass filter were monitored before the procedure. P‐wave amplitude (PWA) and P‐wave terminal force in V1 (PTFV1) Corrected P‐wave duration (PWDc), and P‐wave dispersion (PWDisp), were measured before and after ablation. Results The final analysis included 180 patients, of which 130 (72%) had successful ablations and 53 (30%) had radiofrequency ablation (RF). Males comprised 71% of the patients; the mean age was 60. Demographics were similar between both arms p < 0.001. Patients with failed PVI had increased PWDc after PVI (139–146 ms, p < 0.001) compared to patients with successful PVI. PWA increased significantly after failed PVI (1.6–2 mV, p < 0.001) and successful PVI (1.6–1.8 mV, p = 0.008). PWD (hazard ratio [HR]: 2.5, 95% confidence interval [CI]: 1.4–4.2, p < 0.001) and PWA (HR: 1.7, 95% CI: 1.2–2.9, p = 0.03) were independently associated with PVI failure at 12 months. PWdisp and PTFV1 were not correlated with outcomes. Conclusion Increased PWDc and PWA after PVI were independently associated with failed ablation for PAF, supporting the role of P‐wave parameters in predicting outcomes.